The PDE4 inhibitor tanimilast shows distinct immunomodulatory properties associated with a type 2 endotype and CD141 upregulation - Hoang Oanh Nguyen; Valentina Salvi; Laura Tiberio; Fabrizio Facchinetti; Mirco Govoni; Gino Villetti; Maurizio Civelli; Ilaria Barbazza; Carolina Gaudenzi; Mauro Passari; Tiziana Schioppa; Francesca Sozio; et al. (Journal of Translational Medicine, 2022)
Abstract Background Tanimilast is a novel and selective inhaled inhibitor of phosphodiesterase-4 in advanced clinical development for chronic obstructive pulmonary disease (COPD). Tanimilast is known to exert prominent anti-inflammatory activity when tested in preclinical experimental models as well as in human clinical studies. Recently, we have demonstrated that it also finely tunes, rather than suppressing, the cytokine network secreted by activated dendritic cells (DCs). This study was designed to characterize the effects of tanimilast on T-cell polarizing properties of DCs and to investigate additional functional and phenotypical features induced by tanimilast. Methods DCs at day 6 of culture were stimulated with LPS in the presence or absence of tanimilast or the control drug budesonide. After 24 h, DCs were analyzed for the expression of surface markers of maturation and activation by flow cytometry and cocultured with T cells to investigate cell proliferation and activation/polarization. The regulation of type 2-skewing mediators was investigated by real-time PCR in DCs and compared to results obtained in vivo in a randomized placebo-controlled trial on COPD patients treated with tanimilast. Results Our results show that both tanimilast and budesonide reduced the production of the immunostimulatory cytokine IFN-γ by CD4+ T cells. However, the two drugs acted at different levels since budesonide mainly blocked T cell proliferation, while tanimilast skewed T cells towards a Th2 phenotype without affecting cell proliferation. In addition, only DCs matured in the presence of tanimilast displayed increased CD86/CD80 ratio and CD141 expression, which correlated with Th2 T cell induction and dead cell uptake respectively. These cells also upregulated cAMP-dependent immunosuppressive molecules such as IDO1, TSP1, VEGF-A and Amphiregulin. Notably, the translational value of these data was confirmed by the finding that these same genes were upregulated also in sputum cells of COPD patients treated with tanimilast as add-on to inhaled glucocorticoids and bronchodilators. Conclusion Taken together, these findings demonstrate distinct immunomodulatory properties of tanimilast associated with a type 2 endotype and CD141 upregulation in DCs and provide a mechanistic rationale for the administration of tanimilast on top of inhaled corticosteroids.